The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.55519/jamc-04-s4-11082
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Radial Nerve Injury in Patients With Closed Fracture of Humerus Shaft in High Energy Trauma Cases

Abstract: Background: Fracture of the humerus usually result in radial nerve injury. This study was done with the aim to determine the incidence of Radial Nerve Injury in patients with closed fracture of the humerus shaft in high-energy trauma cases. Methods: This descriptive study was conducted in the Department of Orthopedics and Emergency room, Ghurki Teaching Hospital, Lahore from January  to December 2021 recruiting consecutive such patients. Standard ward protocol was followed to manage the patients initially incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Multiple studies have reported the natural history of median nerve palsy after SCHF 3,17–20 . Although many median palsies after SCHF resolve quickly and spontaneously, several reports of long-term sequelae inconsistent with a neurapraxic injury exist 2,3,8–10,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported the natural history of median nerve palsy after SCHF 3,17–20 . Although many median palsies after SCHF resolve quickly and spontaneously, several reports of long-term sequelae inconsistent with a neurapraxic injury exist 2,3,8–10,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported the natural history of median nerve palsy after SCHF. 3,[17][18][19][20] Although many median palsies after SCHF resolve quickly and spontaneously, several reports of long-term sequelae inconsistent with a neurapraxic injury exist. 2,3,[8][9][10]21 Despite this, contemporary studies continue to describe SCHF-associated median nerve injury as neurapraxic in nature 4,7 when many have an axonotmetic component (Sunderland grade 2 or greater 22 ).…”
Section: Median Nerve Recovery Is Often Incompletementioning
confidence: 99%
“…Fractures have a negative impact on children and young people in multiple ways. [19][20][21][22][23][24][25] Given the increasing trend of methylphenidate uses all over the world over the past 20 years, 3,26 it is necessary to understand the relationship between the risk of fractures and methylphenidate use, to address the knowledge gap and to provide clinical guidance. Although several observational studies using between-subject design 17,18,27,28 have been conducted to investigate the association between the use of methylphenidate and the risk of fractures, they have yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated that the use of methylphenidate is associated with a lower risk of injury, 17,18 given the potential negative bone‐metabolic effect of methylphenidate, it is not clear if methylphenidate is associated with the risk of fractures. Fractures have a negative impact on children and young people in multiple ways 19–25 . Given the increasing trend of methylphenidate uses all over the world over the past 20 years, 3,26 it is necessary to understand the relationship between the risk of fractures and methylphenidate use, to address the knowledge gap and to provide clinical guidance.…”
Section: Introductionmentioning
confidence: 99%